"This Isn’t Something I can Fake": the discourse of disability surrounding Glee! - Ellis, Katie (McFarland, 2013)
This chapter critically examines narratives of disability and audience response to them in the first seasons of Glee, a popular television shows that features series regular characters with a disability. The show has prompted an online engagement from both disability activists on disability specific popular culture blogs, and the general community on non disability specific sites. This chapter is a textual analysis of the programs and a content analysis of viewing practices as articulated through website forums and questions whether viewing practices and interpretations differ according to the presence of disability in the audience.